The Enlightenment of Psychological Counseling Combined with Exercise Therapy on Public Health Pragmatics Classroom - Ruiyu Tang (Revista de Psicología del Deporte (Journal of Sport Psychology), 2023)
This study evaluates the efficacy of psychological counseling (PC) and exercise therapy (ET) in public health pragmatics classrooms. Using a questionnaire, physical exercise scale, and psychological resilience scale, the author divided students with varying mental health (MH) issues into three experimental groups: PC, ET, and control. The findings revealed a significant correlation between the amount of physical activity and the five dimensions of depression, anxiety, tension, self-efficacy, and psychological resilience (r=0.217 0.413, P<0.01). This study found that as college students increased their physical activity, their negative emotional symptoms decreased. It also revealed that the results of the anxiety factor test administered to college seniors after PC and ET differ significantly. Based on a scientific comparison and analysis of experimental data, it has been determined that PC combined with ET can generate significant effects in reducing college students' employment anxiety (EA) and improving their mental health (MH) and that these effects are superior to those of PC intervention alone.